"The holiness of minute particulars": can the community compensate for the schools' shortfalls in affection?. (2nd January 2022) - Rodrigues, Raquel; Amorim, José Pedro; Neves, Tiago
ABSTRACT: In line with the European Union recommendations, Portugal has developed several programs and policies aimed at preventing and reducing school failure and school dropout. This paper focuses on a community intervention project on the social and educational inclusion of children and young people from social housing estates. A 'School Support' practice, consisting of individual and group academic tutoring with basic education students, is presented and discussed. The data collected through a semi-structured interview and two focus groups with parents and socio-educational professionals, enabled us to understand how the School Support Practice is defined and perceived by these actors. The educational, social and individual expectations that the staff and the parents have regarding these students, as well as and the institutional, situational and dispositional barriers that the students have to face in their daily school and social lives were also identified. The research findings highlight, on the one hand, problems such as a fragile relationship between school, children and young people, the poor appreciation of the school by parents, and the low expectations of young people in relation to their academic pathway and school performance. On the other hand, the perspectives of both professionals and parents show that the Project provides some 'holy minute particulars', such as love and positive expectations towards students, that the schools could also provide, as these 'minute particulars' can make the difference.